Autophagy regulates plastid reorganization during spermatogenesis in the liverwort Marchantia polymorpha - Norizuki, Takuya; Minamino, Naoki; Sato, Miyuki; Ueda, Takashi (Frontiers in Plant Science, 2023)
Autophagy is a highly conserved system that delivers cytoplasmic components to lysosomes/vacuoles. Plastids are also degraded through autophagy for nutrient recycling and quality control; however, the involvement of autophagic degradation of plastids in plant cellular differentiation remains unclear. Here, we investigated whether spermiogenesis, the differentiation of spermatids into spermatozoids, in the liverwort Marchantia polymorpha involves autophagic degradation of plastids. Spermatozoids of M. polymorpha possess one cylindrical plastid at the posterior end of the cell body. By fluorescently labeling and visualizing plastids, we detected dynamic morphological changes during spermiogenesis. We found that a portion of the plastid was degraded in the vacuole in an autophagy-dependent manner during spermiogenesis, and impaired autophagy resulted in defective morphological transformation and starch accumulation in the plastid. Furthermore, we found that autophagy was dispensable for the reduction in plastid number and plastid DNA elimination. These results demonstrate a critical but selective role of autophagy in plastid reorganization during spermiogenesis in M. polymorpha.